Classed education trajectories and intimate partnering of international students: a case of Chinese international undergraduate students in the United States. Issue 5 (16th March 2023) - Kim, Yu-Ri
ABSTRACT: The scholarship of international student migration has focused on the difficulties students experience in host countries and often positions them as disadvantaged or marginalised. However, another strand of scholarship has argued that class privilege critically shapes student migration. This discrepancy underlines the need to investigate the reproduction of social hierarchies as coexisting with students' everyday experiences of desire, identity, and inequalities. Analysing the varied manifestations of social class, I argue that international students engage in intimate partnering by strategically utilising their social, economic, and cultural resources and knowledge. Based on in-depth interviews with 30 Chinese international undergraduate students in non-elite and elite colleges in the United States, I demonstrate how classed migration trajectories shape different situations and agencies regarding their partnership options. Even though both groups of students showed co-national homophily, elite schoolers confirmed their class position in opposition to locals while exploring socio-erotic scenes in the host country. Non-elite schoolers remained disadvantaged without attempting status elevation through intimate partnering. More scholarly attention is required to capture the new social hierarchies emerging from transnational student migration.